PERBANDINGAN KINERJA KEUANGAN SEKTOR PARIWISATA, HOTEL DAN RESTORAN, SEBELUM DAN SELAMA COVID-19 - Natalia, Yolanda (Media Akuntansi dan Perpajakan Indonesia, 2022)
This study aims to compare the company’s financial performance before and during Covid as measured by financial ratios of profitability ratios, namely ROA, ROE and NPM. This study is a quantitative study using secondary data collected from 2019 and 2020 annual financial reports. The sample was taken using a purposive sampling method and the samples in this study were 32 tourism, hotel, and restaurant sector companies listed on the IDX in 2019 and 2020. The normality test in this study used the Kolmogorov-Smirnov method and it was concluded that the data were normally distributed will be tested by using paired sample t test and data were both normally distributed will be tested by using wilcoxon signed rank test. The results of this study indicate that there are significant differences before and during the pandemic in ROA, ROE and NPM. There is a significant difference in the profitability ratio due to a decrease in people’s purchasing power during the Covid-19 pandemic which made the company experience a decline in profits.